Medyczna troska o ludzi starych w starożytnym grecko-rzymskim świecie - Longosz, Stanisław (Vox Patrum, 2011)
The article talks about the medical care for older people in ancient Greco-Roman world. The Presocratic theory about warm and moisture was generally admitted in Antiquity. They confected that the human body receives the most portion of warm and moisture with birthday human being and lost this in the course of life. After all, as the elderly is cold and dry. The Treatment of disease rested on prevention of Dehydration and Hypothermia by appropriate diet. The article is consisting of three chapters: The first chapter reminds essential theory about warm and moisture, and presented the types of medicine especially from Hippocrates school. The Hippocratic myth has been popularized by Aristotle. The followers of Hippocrates have detected diseases and afflictions of old age. Their therapy was restricted to apply alimentary diet. The second chapter appears analogous therapy, which had been presented in the patristic period, moved by Galen and his followers. Their therapy included not only alimentary diet, but also massages, gymnastics, walks, baths, moistening and rubbing a diseased part with soil, pharmaceutical, aesthetic or surgical therapy. The third chapter deals with two proposals of old people therapy – Galen’s (diet, exercises, program of old man life and emulation the way of life long-lived people) and Celsius’s (adjustment of diet to the age and season) then surgical, pharmaceutical and aesthetic therapies, which were applying for the meantime. The article concludes that Ancient Christians, in addiction to this issue, created the germs of old people’s homes (Gerontocomia).